GEGURITAN ABIMANYU WIWAHA: ANALISIS STRUKTUR DAN FUNGSI IDA BAGUS ADI RAKA WEDA - Raka Weda, Ida Bagus Adi (Humanis, 2014)
This study discusses the literature in the form of Balinese Traditional geguritan entitled “Geguritan Abimanyu Wiwaha”. Analysis was chosen because the text Geguritan Abimanyu Wiwaha this has relevance in society, especially in the wedding process. In Geguritan Abimanyu Wiwaha it there are ten pupuh and 35 pada. The purpose of this study was to determine the structure of the narrative and the functions contained in the Geguritan Abimanyu Wiwaha. This study reveals the structure and functions contained in Geguritan Abimanyu Wiwaha and literature used is Mr Teeuw, Ratna and Sukada, function theory to analyze the functions contained in Geguritan Abimanyu Wiwaha is Mr Teeuw, Luxemburg, Wellek and Waren. The results in this study is the unfolding of structure in the Geguritan Abimanyu Wiwaha, the formal structure. Functions contained in the Geguritan Abimanyu Wiwaha also was revealed, the function is the function of education which includes religious education are includes a Tattwa (filsafat), Susila (etika) and afirmasi function.
Keywords: geguritan, structure and function